Implementation of COBIT Framework in Improving IT Governance at Indomaret - Daud, Excel; Pepriyani, Nor Lintang; Adriani, Adella; Sabrila, Trifebi Shina; Latif, Abdul; Lindawati, Ratna (LPPM Universitas Sari Mulia, 2024)
This study aims to evaluate the implementation of the COBIT 5 framework in improving information technology governance at Indomaret, one of the largest minimarket chains in Indonesia. COBIT is an internationally recognized framework for IT management and governance that provides structured guidance to ensure that information technology supports business objectives and delivers optimal value. The method used in this study is a case study with a qualitative approach. Dara were collected through in-depth interviews with relevant staff at Indomaret, as well as document analysis and direct observation. The data analysis was conducted to evaluate the alignment between IT processes in Indomaret with best principles and practices proposed by COBIT, specifically in the EDM02 (Ensure Benefits Delivery) and APO06 (Manage Budget and Cost) domains. The evaluation results indicated a gap of 1.39 in the EDM02 domain and 1.15 in the APO06 domain. With an overall average gap score at level 4, it means that at Indomaret, in the EDM02 and APO06 process domains, the findings show that the processes are managed, and the results are determined, controlled, and maintained. For future research, additional process domains in both the governance and management areas could be included, allowing for a more comprehensive audit process using the COBIT framework.